PENGEMBANGAN MEDIA PEMBELAJARAN DIOSIR (DIORAMA SIKLUS AIR) UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA SISWA KELAS V SDN DUREN JAYA XIV - Hida Ria Regita; Awalina Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low level of students' understanding of the concept of water cycle material can be influenced by the lack of innovation in the use of learning media. There is a need for media in the form of a water cycle diorama that presents learning materials through interesting illustrations in the learning process. This research aims to develop DIOSIR media (water cycle diorama) and improve students' understanding of the concept. This research uses the Research and Development (R&D) method with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The feasibility test was carried out by three experts, namely media experts, linguists, and material experts. The media practicality test was carried out using the educator's response, and the media use interest test was carried out using the student's response. The effectiveness test was carried out using pre-test and post-test for grade V students. The results of the study showed that the DIOSIR learning media (water cycle diorama) was declared